The weight-adjusted waist index and frailty: A cohort study from the China Health and Retirement Longitudinal Study - Jinhua Luo; Hailian Deng; Yueying Wu; Tuming Zhang; Yuying Cai; Yu Yang (Elsevier, 2024)
Objectives: This cohort study's aim was to assess the association between the weight-adjusted waist index (WWI) and frailty among middle-aged and elderly individuals in China. Methods: Seven-year complete follow-up data from 10,349 adults aged ≥45 years, initially surveyed in 2 011 in the China Health and Retirement Longitudinal Study, were analyzed, including clinical demographic characteristics, anthropometric indices, frailty scores, and relevant covariates. The WWI was calculated as waist circumference divided by the square root of the body weight. Frailty was evaluated using the Frailty Index. Relationships between the WWI and frailty were evaluated via Cox proportional hazards modeling. Receiver operating characteristic curve analyses assessed the effectiveness of obesity-related indicators in predicting frailty. Results: Over a median 84-month follow-up period, frailty occurred in 23.7% (2453/10,349) of participants. After potential confounder adjustment, the WWI positively correlated with frailty (adjusted hazard ratio: 1.14; 95% confidence interval: 1.08-1.20; p < 0.001). After WWI-stratification into quartiles based on frailty and covariate adjustment, regression analyses were conducted; the adjusted hazard ratios exhibited a significant upward trend (p < 0.001). The subgroup analyses revealed higher positive correlations between the WWI and frailty in males and those aged ≥65 years and lower correlations in those with a high school or higher educational level and in married or cohabiting individuals. The strong positive correlation was unaltered in the other subgroup analyses. The WWI outperformed all other obesity-related indicators as a frailty predictor. Conclusions: The WWI is a dependable and innovative obesity-related predictor of frailty and could help in mitigating its development.